A generational comparison of problem gambling and gambling attitudes among older adult gambling venue patrons. Issue 1 (2nd January 2019) - van der Maas, Mark; Matheson, Flora I.; Turner, Nigel E.; Hamilton, Hayley A.; Mann, Robert E.; McCready, John
ABSTRACT: Gambling is a popular leisure activity for older adults (55+), and existing research suggests that overall older adults are less prone to problem gambling compared to younger cohorts. People born after World War II are now beginning to reach retirement age. The purpose of this article was to explore age-related cohort differences between people born from 1943 to 1960 compared to those born from 1925 to 1942 in their attitudes and behaviours related to gambling. This study employs a large sample (2103) of older adults collected at gambling locations across Southern Ontario, Canada in 2013. Comparisons were made using Pearson's chi-squared tests for categorical variables and independent samples t-tests for continuous variables with logarithmic transformations for highly-skewed variables. Those of the 1943 to 1960 cohort showed significantly higher problem gambling scores and per visit spending, but lower numbers of visits per year. There was no discernible pattern between cohorts in terms of attitudes toward gambling. Assumptions of lower risk of problem gambling among older adults will have to be re-evaluated as the post-war generation becomes an ever greater proportion of older adults.